Engineering information security : - Jacobs, Stuart. (Wiley, 2016)
This book begins by considering the importance of information security. Legal, technical, competitive, criminal, and consumer forces and influences that are rapidly changing our information dependent society are also discussed. Concepts of systems engineering are explored, as well as the value they provide to new products and services along with the maintenance and evolution to existing products and services. A discussion of security services follow along with what technical and procedural controls instantiate these services. Network protocols are examined focusing on exploitable vulnerabilities. An in-depth discussion of computer security capabilities is provided followed by consideration of modern networking security controls. The book concludes by discussing operations security as part of information security governance.